Esophageal Rupture Presenting with ST Segment Elevation and Junctional Rhythm Mimicking Acute Myocardial Infarction - Wytch Rigger (Hindawi Limited, 2021)
Esophageal rupture is a rare but potentially fatal cause of chest pain. The presentation is variable and can mimic other conditions such as aortic dissection, pulmonary embolism, and myocardial infarction (MI). A 71-year-old male with a history of coronary artery disease presented to the ED with complaints of acute chest pain and respiratory distress. Over the next 48 hours, the patient developed dynamic ST segment changes on surface electrocardiogram mimicking an inferolateral ST segment elevation MI accompanied by a junctional rhythm. Curiously, his cardiac enzymes remained negative during this time, but his clinical status continued to deteriorate. A subsequent CT scan demonstrated a lower esophageal rupture, and the patient underwent successful endoscopic stenting. While rare, prompt recognition of esophageal rupture is imperative to improving morbidity and mortality. While esophageal rupture has been noted to cause ST segment elevation before, this appears to be the first case associated with a junctional rhythm.